Oxidative Stress Tolerance by Calcium and Histidine in Two Tomato Cultivars Under Nickel Stress - Mozafari H.; Asrar Z.; Rezanejad F.; Pourseyedi S.; Yaghoobi M.M. (Journal of Stress Physiology & Biochemistry, 2014)
We investigated calcium (Ca) and L-histidine (His) interaction on nickel (Ni)-induced oxidative stress tolerance in two tomato (Solanum lycopersicum Mill.) cultivars including Cal-J N3 and Petoearly CH. CaCl2 (0 and 300 µM) and L-histidine (0 and 300 µM) effects on the oxidative responses in these cultivars cultured were compared in the hydroponic media under Ni stress (NiSO4; 0,150 and 300 µM). The activities of antioxidative enzymes including catalase (CAT), guaiacol peroxidase (GPX), ascorbate peroxidase (APX), superoxide dismutase (SOD) and total content of proteins, malondialdehyde (MDA), other aldehydes, H2O2, Ca2+, Ni2+, ascorbate (ASC), dehydroascorbate (DHA) and electrolytes leakage (EL) were determined. The obtained results indicated that the application of Ca and His generally reduced oxidative markers such as the contents of EL, H2O2, MDA and activity of CAT as well as the Ni2+content of root and shoot organs under nickel toxicity, while application of Ni treatment without Ca+His increased these oxidative parameters and accumulation of Ni2+, compared to the control. Applying Ni without Ca and His has resulted in reduction of GPX, APX and SOD activities as well as concentrations of root and shoot Ca2+and ASC in the two mentioned cultivars. Application of Ca and His lead to the elevated contents of Ca2+ and ASC, increased activities of GPX, APX and SOD as well as inhibition of Ni2+ accumulation differently in both cultivars. Ca and His also alleviated the adverse effects of Ni stress on the selected investigated parameters especially in Petoearly CH cultivar. Thus, interaction of Ca and His appeared to improve adaptive responses to Ni stress leading to decreasing Ni-induced oxidative stress in the tomato plants. Therefore, our results suggest that Ca+His alleviated nickel-induced oxidative stress by uptake and inhibition of translocation of Ni2+ plus Ni chelating mechanism improvement in the tomato cultivars.